LONG-TERM OUTCOMES OF COMMON BILE DUCT INJURY: A COMPARISON BETWEEN OPEN AND LAPAROSCOPIC CHOLECYSTECTOMY.: JPUMHS;2024:14:03,44-50.http://doi.org/10.46536/jpumhs/2024/14.03.534 - Ahmed Halepoto1, Maimoona Khushk2, Humaira Yousuf3, Shahnawaz Leghari4, Fouzia Nusrat pathan5, Sajjad Hussain Qureshi6 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND:Common bile duct CBD injury is a significant complication of cholecystectomy, occurring more frequently in laparoscopic procedures than in open surgeries. The purpose of this study is to compare the postoperative long term outcomes of CBD injury treated by both surgical procedures.OBJECTIVE: In order to compare the incidence of CBD injuries and postoperative complications, reintervention rates, and quality of life outcome between patients undergoing open and laparoscopic cholecystectomy. MATERIAL AND METHODS:This prospective study included 132 patients 66 open cholecystectomies, 66 laparoscopic cholecystectomy at Surgical Department within Surgical Units I, II, and III of Peoples Medical College Hospital Nawabshah from 1st February 2024 to 31st July 2024. Data were collected on demographic information, ethnicity, injury characteristics, follow up outcomes and quality of life in terms of the SF 36 questionnaire with ethical approval, after which data were processed. All statistical analyses were performed using SPSS version 21.0 and the appropriate tests were performed for comparison. RESULTS:There were no significant differences in the incidence of CBD injuries, postoperative complications including cholangitis and biliary stricture, or reintervention rates at 24 months. The median hospital stay was longer for open cholecystectomy 8 days than for laparoscopic cholecystectomy 5 days; p=0.001. Scores of quality of life were similar, without significant statistical differences in any of the domains. CONCLUSION: Despite the shorter duration of hospital stay in laparoscopic procedures, the long-term complication rates, the rates of reintervention, and the quality of life scores were similar for the two approaches.